2014
DOI: 10.3906/biy-1312-94
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning effect of cytokinins on in vitro multiplication of embryonic node of grass pea (Lathyrus sativus L.) cultivar Gürbüz

Abstract: Lathyrus sativus L. (grass pea) is an important grain legume crop grown all over the world. It is very recalcitrant and difficult\ud to regenerate under in vitro conditions. The present study determined the effect of preconditioning of cytokinins [10 and 20 mg L–1\ud thidiazuron (TDZ) and 2-isopentenyl adenine (2iP)] and postconditioning of dissimilar levels of TDZ-indole-3-butyric acid (IBA)\ud and 2iP-IBA on in vitro shoot multiplication using embryonic node explants. The results showed that preconditioning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
2
9
1
Order By: Relevance
“…These findings are contrarily to the previous reports given by Aasim et al (2012Aasim et al ( , 2013 which might be due to late shoot induction from callus in this study which was not observed in chickpea previously. Similarly, negative effects of inceased BAP concentration with NAA has been reported for preconditioned embryonic node of grass pea (Barpete et al, 2014). The results also confirmed the clear effects of postconditioning concentrations on shoot length and in line with Aasim et al (2009Aasim et al ( , 2010 in cowpea and chickpea (Aasim et al, 2011 and.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…These findings are contrarily to the previous reports given by Aasim et al (2012Aasim et al ( , 2013 which might be due to late shoot induction from callus in this study which was not observed in chickpea previously. Similarly, negative effects of inceased BAP concentration with NAA has been reported for preconditioned embryonic node of grass pea (Barpete et al, 2014). The results also confirmed the clear effects of postconditioning concentrations on shoot length and in line with Aasim et al (2009Aasim et al ( , 2010 in cowpea and chickpea (Aasim et al, 2011 and.…”
Section: Discussionsupporting
confidence: 75%
“…This phenomenon of shoot regeneration from callus is not reported earlier by other researchers worked on preconditioning followed by postconditioning of explants (Aasim et al, 2009(Aasim et al, , 2011(Aasim et al, , 2012(Aasim et al, and 2013Barpete et al, 2014). Analysis of variance showed statistically insignificant effects of preconditioning dosage on callus and 100% shoot regeneration frequency in agreement with (Aasim et al, 2009) and embryonic axis (Aasim et al, 2010) of cowpea, mature embryo and embryonic axis (Aasim et al, 2011) and plumular apices (Aasim et al, 2013) of chickpea, plumular apices of lentil (Aasim et al, 2012) and (Barpete et al, 2014) from embryonic node of lathyrus preconditioned with 20 mg/l TDZ. Contrarily, variable response of cotyledonary node of dwarf chickling pulse treated with cytokinin on callus and shoot induction has been reported by Saglam (2012).…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations